GREEN ENERGY-BASED HOTEL MANAGEMENT CONCEPT - Anvarova , Muhsinakhon (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This study explores the concept of green energy-based hotel management as a strategic framework for achieving sustainability in the hospitality industry. With the growing global emphasis on renewable energy and environmental conservation, hotels are increasingly expected to minimize their ecological footprint while maintaining operational efficiency. The research adopts a mixed-method approach, combining quantitative data from hotel energy audits and qualitative insights from managerial interviews. The findings reveal that hotels integrating renewable energy systems—such as solar and geothermal technologies—achieve significant reductions in operational costs, carbon emissions, and energy consumption. Additionally, the study highlights positive managerial attitudes toward sustainability, noting that environmentally responsible practices enhance brand reputation and customer satisfaction. However, financial and technical challenges remain major barriers to full-scale adoption. The paper concludes that green energy-based management not only strengthens the competitiveness of hotels but also aligns with the United Nations Sustainable Development Goals (SDGs), particularly in promoting clean energy and responsible production. The study offers recommendations for policy enhancement, technological innovation, and capacity development to facilitate broader adoption of green energy within the hospitality sector.